Using co‐design to develop a culturally responsive reproductive health learning resource for Aboriginal and Torres Strait Islander youth. (1st September 2020) - Gilbert, Emily; Collins, Raelene; Webster, Vanya; Boyd, Nicole; Maple‐Brown, Louise; Boyle, Jacqueline; Smith‐Vaughan, Heidi
Abstract: Issue addressed: Healthy behaviours prior to conception can improve pregnancy outcomes and intergenerational health. Adolescence is an important period to promote preconception health, but education resources need to be age and culturally appropriate. Few studies have addressed preconception awareness and knowledge among Aboriginal and Torres Strait Islander youth, and few culturally appropriate resources exist. Methods: A mixed methods, co‐design process engaging Aboriginal and Torres Strait Islander youth and an Indigenous Reference Group (IRG). Additionally, a survey was carried out to identify preconception health awareness and interest among a broader youth audience. Results: Several main themes emerged from consultation meetings with youth reflecting an awareness of preconception health, but limited understanding. Youth revealed an interest in fertility, and a need for more information on lifestyle factors associated with infertility. Preconception information related to the opposite sex was seen as important as well as information incorporating current local knowledge and world views. Among the survey respondents, 46% (11/24) had a pre‐existing understanding of preconception health. Optimising lifestyle behaviours prior to pregnancy was perceived as important for women (21/24; 88%), but less so for men (16/24; 67%), highlighting a gap in knowledge regarding the importance of preconception health for men. Conclusion: The co‐designed resource "Getting healthy before pregnancy" is available in print and electronically, with illustrations and synchronised audio overlay in Aboriginal English or East‐side Kriol. The resource includes information on preconception health and behavioural risk factors. So what: We present a co‐designed preconception health resource for evaluation with Aboriginal and Torres Strait Islander youth.